Acute Effects of Stretching Types during Warm up on Selected Skill Related Performances at Ethiopian Defense Sport Club Middle Distance Athlete - Kasahun Kiminad , Sintayehu; Kebede Legesse (Ph.D), Amensisa (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
The purpose of this study was determined the acute effect of stretching types during warm up on selected skill related performances and its association with the occurrence of injury during training and competition at Ethiopian defense athletics sport club. The total athletes selected for this study were (N=30) fourteen male and fourteen female with age range of 18-24. The athletes were oriented about the test and its objective, There was no control group in this study. An experimental group used for intervention after grouped for three. The athletes were assigned randomly for three groups having different week of stretching introduction during warm up but same training. Every group will have the intervention of no stretching, static and dynamic stretching weeks for three times interchangeably. The intervention lasts for nine weeks. After the intervention from one stretching type to the others the tests were taken at the fifth day of every week. One-way repeated measures ANOVA were conducted to compare scores on all tests across groups while repeated measure of ANOVA was employed to check the performance difference of the athletes while having different stretching week. Based up on the test there is a significant difference in athletes, agility, Broad Jump and 400m performance during dynamic stretching than static and No stretching. Better Activeness were reported during Dynamic Stretching-3 (DS-3) mean=4.46±.33, static stretching-3 (SS-3) mean=4.23±.42, and No Stretching-3 (NS-3) mean=3.54±.88. 7. In addition to this Better Pace Performance test result shows that DS-3 mean=4.55±.32, SS-3 mean=4.34±.56, and NS-3 mean=4.34±.27. Furthermore the Consistency of Performance test result shows that DS-3 mean= 4.63±.42, SS-3mean=4.63 ±.42, and NS-3 mean=4.42 ± .28. , There was a significant effect for Activeness/Direct Enrollment scores During Dynamic stretching time training. Activeness average score which is close to very good and followed by static stretching which is close to good. There is also a significant decline for Activeness/Direct Enrollment on athletes during no stretching time which is less than good. On the other hand there was no significant effect for Better Pace/Consistency and Consistency of Performance but average score mean of dynamic stretching has shown better result than static stretching and no stretching. From the data collected it is concluded that the dynamic stretching has a better effect on agility broad jump and, 400m performance followed by static and No stretching. A significant better accomplishment of Activeness during dynamic stretching was recorded followed by static and No stretching .Thus it is concluded that overall dynamic stretching can support for better performance than static and no-stretching performance.